2012
DOI: 10.2147/ijn.s34365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on solubility, dissolution rate, and oral bioavailability: evaluation using coenzyme Q10 as naked nanocrystals

Abstract: In this paper work, four naked nanocrystals (size range 80–700 nm) were prepared without any surfactant or polymer using the solvent/nonsolvent method. The effects of particle size on their solubility, dissolution, and oral bioavailability were investigated. Solubility and dissolution testing were performed in three types of dissolution medium, and the studies demonstrated that the equilibrium solubilities of coenzyme Q 10 nanocrystals and bulk drugs were not affected by the dissolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…In the case of the 1 wt% L-HAp dispersion, a part of the HAp nanoparticles remained on the PDMA overlapped area possibly because of their large size and morphology; i.e., because of the smaller diffusion coefficient of the larger rod-shaped nanoparticles [39]. Eventually the remaining L-HAp nanoparticles could promote a stronger adhesion compared to the S-HAp and M-HAp nanoparticle dispersions at low concentrations of 2 and 4 wt%.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the 1 wt% L-HAp dispersion, a part of the HAp nanoparticles remained on the PDMA overlapped area possibly because of their large size and morphology; i.e., because of the smaller diffusion coefficient of the larger rod-shaped nanoparticles [39]. Eventually the remaining L-HAp nanoparticles could promote a stronger adhesion compared to the S-HAp and M-HAp nanoparticle dispersions at low concentrations of 2 and 4 wt%.…”
Section: Discussionmentioning
confidence: 99%
“…method involved mechanical activation of both the drugs using a ball mill and optimisation of milling time and speed after taking many trials in the view of conversion of a crystalline drug into amorphous counterpart and particle size reduction enhancing solubility and dissolution. [36][37][38][39] In COAM, saturation solubility of IB in distilled water was altered after ball milling and was different for all dose combinations with PA, whereas, it was invariably same for PA, as depicted in Table 1. Maximum increase in aqueous solubility of IB was seen in 500 mg: 200 mg dose ratio (COAM 1), indicating role of PA and coamorphism towards solubility enhancement of IB, even if its solubility is pH dependent.…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Smentioning
confidence: 99%
“…5. It is known that particle size reduction enhances dissolution of drugs [36][37][38][39][40] but, is not a sole reason for improved dissolution. This can be explained by the dissolution profile of BMP and BMI, in which the dissolution of individually milled drug was not improved.…”
Section: In-vitro Dissolution Studiesmentioning
confidence: 99%
“…Sun et al prepared coenzyme Q10 nanocrystals with different particle sizes (80 nm, 120 nm, 400 nm, or 700 nm) and investigated the in vitro dissolution of the nanosuspension formulations containing coenzyme Q10, and bulk drugs in three different dissolution media. The results obtained from these dissolution studies showed that dissolution rate of coenzyme Q10 was clearly affected by the particle size of drug [21]. In another study, Hecq et al prepared nanoparticles of poorly water soluble drug nifedipine, by high pressure homogenization to enhance its solubility and dissolution rate.…”
Section: Dissolution Studymentioning
confidence: 99%